2018
DOI: 10.1021/acscentsci.8b00526
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Interplay of Catechol Binding and Polymer Hydrophobicity in a Mussel-Inspired Elastomeric Adhesive

Abstract: Marine organisms such as mussels have mastered the challenges in underwater adhesion by incorporating post-translationally modified amino acids like l-3,4-dihydroxyphenylalanine (DOPA) in adhesive proteins. Here we designed a catechol containing elastomer adhesive to identify the role of catechol in interfacial adhesion in both dry and wet conditions. To decouple the adhesive contribution of catechol to the overall adhesion, the elastomer was designed to be cross-linked through [2 + 2] photo-cycloaddition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 81 publications
0
92
0
Order By: Relevance
“…The CFPs are also capable of the adhesion at wet or underwater situations, although the bonding strength is much lower because of the formation of hydrated cation layers. [ 17 ] White and Wilker [ 18 ] and Joy and co‐workers [ 19,20 ] incorporated monomers with electrostatic charges or aliphatic pendants into CFPs, achieving underwater bonding strength of 0.4 MPa on aluminum and 0.65 MPa on glass, respectively. By adjusting the polarity [ 21 ] or the hydrophilicity [ 22 ] of CFP backbones, Wan et al reported improved bonding strength of 1.13 and 1.33 MPa on glass substrates.…”
Section: Methodsmentioning
confidence: 99%
“…The CFPs are also capable of the adhesion at wet or underwater situations, although the bonding strength is much lower because of the formation of hydrated cation layers. [ 17 ] White and Wilker [ 18 ] and Joy and co‐workers [ 19,20 ] incorporated monomers with electrostatic charges or aliphatic pendants into CFPs, achieving underwater bonding strength of 0.4 MPa on aluminum and 0.65 MPa on glass, respectively. By adjusting the polarity [ 21 ] or the hydrophilicity [ 22 ] of CFP backbones, Wan et al reported improved bonding strength of 1.13 and 1.33 MPa on glass substrates.…”
Section: Methodsmentioning
confidence: 99%
“…[9] The commercially available epoxy resins [10] and polyurethanes [11] are reported to demonstrate strong underwater adhesion, but long time of curing is usually required. [15][16][17] The finding of universality of catechol chemistry for wet adhesion has provided a valuable biomimetic source to develop diverse adhesives for use in aqueous environments. [5,12] In addition, electrostatic and hydrophobic interactions were also proved to contribute to enhanced underwater adhesion, but the adhesion strength was relatively poor.…”
mentioning
confidence: 99%
“…[13,14] In nature, many organisms, such as mussels, barnacles, and castle worms, have evolved an unparalleled mechanism to perfectly tackle the underwater adhesion problem. [15][16][17] The finding of universality of catechol chemistry for wet adhesion has provided a valuable biomimetic source to develop diverse adhesives for use in aqueous environments. However, several problems, such as the complexity of administration, release of harmful organic solvents, [18,19] long-term curing, [2] need for oxidant addition, [20,21] and low adhesion strength, [18,22] may hamper the actual applications of these bioinspired adhesives.…”
mentioning
confidence: 99%
“…After several washouts, the SEM images shown in Figure 4d confirmed that MSNs‐TA@PDA‐Zn nanocomposites have excellent adhesion performance, which was due to an abundance of catechol groups in PDA, and they interacted with substrate through hydrogen bonding. [ 40 ] This could effectively prevent the pesticide particles from rolling off. This behavior was similar to those reported in previous studies.…”
Section: Resultsmentioning
confidence: 99%